The Wage Effects of Polytechnic Degrees: Evidence from the 1999 China Higher Education Expansion - Li Dai; Pedro S. Martins (Global Labor Organization (GLO), 2024)
While the wage effects of vocational versus academic secondary education are well documented, there is little evidence on how polytechnics degrees pay off compared to university degrees. In this paper, we estimate the polytechnic degree wage effect in China, drawing on an unprecedented higher education expansion initially focused on universities and only later covering polytechnics. We find a large polytechnic wage penalty, of 35%, larger than what could be driven by the shorter duration of these degrees. While this result is robust to several checks, the penalty is found to be more pronounced for workers of lower earnings potential, when using IV-QR methods. Our results are consistent with a significant human capital gap of polytechnic degrees compared to university degrees.
Keywords: I23; I26; J24; 330; Returns to education; Polytechnics; Higher Education Expansion; China